Femoropopliteal Artery Stent Thrombosis: Report From the Excellence in Peripheral Artery Disease Registry. (February 2016) - Banerjee, Subhash; Sarode, Karan; Mohammad, Atif; Gigliotti, Osvaldo; Baig, Mirza S.; Tsai, Shirling; Shammas, Nicolas W.; Prasad, Anand; Abu-Fadel, Mazen; Klein, Andrew; Armstrong, Ehrin J.; Jeon-Slaughter, Haekyung; et al.
Abstract : Background—: There are limited data on femoropopliteal artery stent thrombosis (ST), which is a serious adverse outcome of peripheral artery interventions. Methods and Results—: Index procedures resulting in femoropopliteal ST were compared with stent procedures without subsequent ST in the Excellence in Peripheral Artery Disease registry. The study data had a total of 724 cases of stent procedures and 604 unique patients. Femoropopliteal ST occurred in 26 of 604 patients (4.3%) over a median follow-up of 6 months post procedure. ST was more likely to occur in men (96.3% versus 82.2%; P =0.026) and to have an initial intervention for chronic total occlusions (88.5% versus 64.0%; P =0.01). There was no significant difference in ST between drug-coated and bare-metal stents (4.4% versus 3.4%; P =0.55), but the rate of ST was significantly higher with self-expanding covered stent grafts compared with bare-metal stents (10.6% versus 3.4%; P =0.02). ST was significantly associated with an increased risk of 12-month major adverse limb events (hazard ratio, 4.99; 95% confidence interval, 2.31–10.77; P <0.001) compared with no ST. On multivariate analysis, treatment of chronic total occlusion lesions (odds ratio, 3.46; 95% confidence interval, 0.98–12.20; P =0.05) and in-stent restenosis lesions (odds ratio, 5.30; 95% confidence interval, 1.83–15.32; P =0.002) were independently associated with an increased risk of ST. Conclusions—: In a multicenter peripheral interventional registry, femoropopliteal ST occurred in 4.3% of patients who underwent stent procedures, and it was associated with treatment of chronic total occlusions and in-stent restenosis lesions, and had higher 12-month major adverse limb events. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01904851. Abstract : Supplemental Digital Content is available in the text.